A Comparative Life-Cycle Assessment of Two Cogeneration Plants - Siddiqui, Osamah; Dincer, Ibrahim (WILEY-V C H VERLAG GMBH, 2020)
Herein, a comparative energetic and life-cycle assessment (LCA) study is performed on coal and natural gas-based combined heat and power cogeneration plants. Different types of power plants, including gas turbine, steam turbine, and combined-cycle plants, are considered. Three types of LCA methodologies, including CML 2001, TRACI, and ReCiPe, are used to analyze the life-cycle environmental impacts of each plant. The coal-based cogeneration plant is found to entail the comparatively lowest life-cycle energy efficiency of 43.6%, and the natural gas-based combined-cycle cogeneration plant is found to have the highest efficiency of 59.6%. Furthermore, the coal-based life cycle is also found to entail the highest life-cycle environmental impacts comparatively. According to CML 2001, it entails a global-warming potential of 0.229 kg CO2eq MJ(-1) and an acidification potential of 7.03E-4 kg SO2eq MJ(-1). The natural gas-fired boiler-type cogeneration plant is observed to have a comparatively higher toxicity and eutrophication potential of 2.72E-4 kg DCBeq MJ(-1) and 2.78E-5 kg PO4eq MJ(-1), respectively. The lowest overall life-cycle environmental impacts comparatively are found to be associated with the natural gas-based combined-cycle cogeneration plant.
Keywords: cogeneration; efficiency; environmental impacts; life-cycle assessment; NATURAL-GAS; POWER-GENERATION; COAL; SYSTEMS; SNG; Energy & Fuels